2018
DOI: 10.1016/j.neuroscience.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Human Apolipoprotein E Genotype Differentially Affects Olfactory Behavior and Sensory Physiology in Mice

Abstract: Apolipoprotein E (ApoE) is an important lipid carrier in both the periphery and the brain. The ApoE ε4 allele (ApoE4) is the single most important genetic risk-factor for Alzheimer's disease (AD) while the ε2 allele (ApoE2) is associated with a lower risk of AD-related neurodegeneration compared to the most common variant, ε3 (ApoE3). ApoE genotype affects a variety of neural circuits; however, the olfactory system appears to provide early biomarkers of ApoE genotype effects. Here, we directly compared olfacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Together, these previous findings may help to explain the cognitive impairments exhibited by mice lacking ApoE or expressing ApoE4 particularly in spatial learning/memory and in olfactory memory, two neurogenic-dependent behaviors [63][64][65][66][67][68][69][70][71]. Although it remains unclear whether recovery from injuries such as TBI is dependent on neurogenesis in general and ApoE state in particular, the present study adds needed insight into a potential mechanism linking the two.…”
Section: Plos Onesupporting
confidence: 54%
“…Together, these previous findings may help to explain the cognitive impairments exhibited by mice lacking ApoE or expressing ApoE4 particularly in spatial learning/memory and in olfactory memory, two neurogenic-dependent behaviors [63][64][65][66][67][68][69][70][71]. Although it remains unclear whether recovery from injuries such as TBI is dependent on neurogenesis in general and ApoE state in particular, the present study adds needed insight into a potential mechanism linking the two.…”
Section: Plos Onesupporting
confidence: 54%
“…Hence, it is not surprising that impairments in performance in hippocampus-dependent behavioral tasks in mice deficient in ApoE or ones carrying the human ApoE4 are observed. Several studies have demonstrated that the presence of human ApoE4 or the absence of rodent ApoE impaired odor memory, Morris water maze task, and contextual fear-conditioning tasks ( Masliah et al, 1997 ; Grootendorst et al, 2001 ; Peister et al, 2006 ; Rodriguez et al, 2013 ; Salomon-Zimri et al, 2015 ; Peng et al, 2017 ; East et al, 2018 ). Further studies are required to determine the electrophysiology of newborn neurons under such genetic backgrounds to see whether they mimic the deficits in behavioral performance.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms appear to drive the pathogenic effects of the APOE4 allele in the brain, including enhancing Aβ deposition while reducing Aβ clearance and degradation; modulating synaptic integrity; modulating cholesterol levels in the brain and the availability of cholesterol and other lipids to neurons; and inducing changes in reactive O 2 scavenging in the CNS Ma et al, 1994;Bales et al, 1997;Higgins et al, 1997;Haan et al, 1999;Holtzman et al, 2000;Shibata et al, 2000;Bu, 2009;Kim et al, 2009;Kolovou et al, 2009;Andrews-Zwilling et al, 2010;Verghese et al, 2011;Villemagne et al, 2011;Leung et al, 2012;Mahley and Huang, 2012;Andrews et al, 2013;Liu et al, 2013;Reinvang et al, 2013;Zlokovic, 2013;Rodriguez et al, 2014). In the absence of a dementia diagnosis, human APOE4-carriers still display structural and functional differences within regions of the hippocampus and cortex, and cognitive decline compared to age-matched non-carriers (Bookheimer and Burggren, 2009;Filippini et al, 2009;Olofsson et al, 2010;Sheline et al, 2010;Wisdom et al, 2011;Liu et al, 2013;Di Battista et al, 2016), and mouse models show cognitive deficits linked to APOE4 expression without AD pathology (Leung et al, 2012;Peng et al, 2017;East et al, 2018).…”
Section: Exosome Production Is Compromised By Apoe4 Expressionmentioning
confidence: 99%